A method for preparing biomass fiber-reinforced asphalt pavement material with rutting resistance

By using the porous eggshell powder and composite gel layer of load waste oil in the asphalt pavement material to enhance the interaction of glass microfin beads and asphalt, and spray nano -carbon powder dispersing liquid on the surface of the modified glass micro beads, solve the asphalt pavement surface The problem of poor carrier -resistant performance and biomass fiber degradation have achieved higher rutors and high temperature resistance.

CN118724509BActive Publication Date: 2025-01-24SHANDONG JIAOTONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411224736.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-01-24
Estimated Expiration
2044-09-03

AI Technical Summary

Technical Problem

Under the action of high temperature and channelized traffic, asphalt pavement has poor rut resistance, resulting in permanent deformation of the asphalt pavement structure layer and reducing the strength of the overall structure of the pavement; during the asphalt mixing process, high temperatures can easily lead to biomass fibers. Degradation affects the rut resistance of asphalt pavement; although glass microbeads can prevent heat transfer, they have poor binding force with asphalt matrix and are prone to breakage.

Method used

By introducing porous eggshell powder with load waste oil in the asphalt pavement material to form a composite gel, and the composite gel layer is deposited on the surface of biomass fibers, the interaction of glass micro beads and asphalt is enhanced. Nano -carbon powder dispersed liquid to form a uneven rough surface.

Benefits of technology

It improves the rutting resistance and high temperature resistance of asphalt pavement materials, enhances the compressive strength and thermal aging properties of the material, and avoids the problems of biomass fiber degradation and glass microsphere breakage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a method for preparing a biomass fiber-reinforced anti-rutting asphalt pavement material, which belongs to the technical field of anti-rutting asphalt pavement materials, and comprises the following components: 60-80 parts of coarse aggregate, 20-40 parts of fine aggregate, 10-20 parts of 70# matrix asphalt, 6-8 parts of modified biomass fiber, 3-5 parts of limestone crushed stone, and 2-3 parts of composite filler. A gel layer is formed on the surface of the biomass fiber to avoid the high temperature that easily causes the degradation of the biomass fiber during the asphalt mixing process; the composite gel is filled into the asphalt gap along with the biomass fiber, and the composite gel can be combined with the polar components in the asphalt to form a network mixed structure in the asphalt matrix, thereby improving the resilience of the asphalt pavement material, increasing its anti-rutting ability, and increasing the interaction and integrity of the asphalt system; the surface of the modified glass microsphere forms a concave-convex rough surface, and when subjected to external force, the concave-convex structure can absorb stress and prevent the expansion of asphalt cracks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rutting-resistant asphalt pavement materials, and in particular to a method for preparing a biomass fiber-reinforced rutting-resistant asphalt pavement material. Background Art

[0002] Asphalt pavement refers to various types of pavement that are paved by adding road asphalt materials, fillers, additives, etc. to mineral materials. The asphalt binder improves the ability of paving aggregate to resist damage to the road surface caused by driving and natural factors, making the road surface smooth, dust-free, waterproof, and durable. It has good elasticity and plastic deformation capacity, can adapt to stress changes caused by various loads, and effectively absorb and disperse the impact force generated by vehicle driving, thereby reducing driving vibration, reducing the noise between tires and the road surface, and improving driving comfort. It is necessary to consider that in hot weather, asphalt pavement will absorb a lot of heat, causing the asphalt to soften and increase its viscosity. When it is subjected to a large car load, it is very easy to cause permanent deformation, causing the road surface to crack and then produce rutting.

[0003] Under the influence of high temperature and channelized traffic, the rutting resistance of asphalt pavement is poor, which leads to permanent deformation of the structural layer of the asphalt pavement and reduces the strength of the overall structure of the pavement. By adding inorganic powders and biomass fibers to the asphalt pavement material, the rutting resistance of the asphalt can be effectively improved. However, during the asphalt mixing process, the high temperature can easily lead to the degradation of biomass fibers, affecting the rutting resistance of the asphalt pavement. Glass microbeads can effectively prevent the transfer of heat to the asphalt pavement, improve the thermal resistance of the asphalt pavement material, and avoid rutting caused by excessive internal temperature of the asphalt pavement. However, the bonding strength between the glass microbeads and the asphalt matrix is ​​poor, and the glass microbeads are easily broken when subjected to external forces. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a biomass fiber reinforced asphalt pavement material with rutting resistance: porous eggshell powder is loaded with waste engine oil, and the asphalt component is easily volatile during the aging process, so that the waste engine oil in the eggshell powder loaded with waste engine oil is released into the asphalt, so that the content of saturated components and aromatic components in the asphalt is kept stable, thereby reducing the aging degree of the asphalt; the eggshell powder loaded with waste engine oil is embedded in the porous gel, so as to improve the compressive strength of the eggshell powder loaded with waste engine oil, and avoid the eggshell powder being broken due to external stress in the asphalt pavement material, which affects the anti-aging performance of the asphalt pavement; the composite gel is deposited on the biomass fiber The surface of the biomass fiber is modified by the bioadhesive, and a gel layer is formed on the surface of the biomass fiber, which has good high temperature resistance and avoids the degradation of the biomass fiber due to high temperature during the asphalt mixing process; the glass microspheres are modified by the bioadhesive surface and then reacted with the prepolymer, so that the prepolymer containing carbamate and alkane groups is grafted on the surface of the glass microspheres, which enhances the interaction between the glass microspheres and the asphalt and improves the thermal aging performance; the nano-carbon powder dispersion is sprayed on the surface of the modified glass microspheres to form a concave-convex rough surface on the surface of the modified glass microspheres. When subjected to external force, the concave-convex structure can absorb stress, prevent the expansion of asphalt cracks, and improve the compressive strength.

[0005] The technical problems to be solved by the present invention are as follows: under the action of high temperature and channelized traffic, the rutting resistance of asphalt pavement is poor, resulting in permanent deformation of the structural layer of the asphalt pavement, reducing the strength of the overall structure of the pavement; during the asphalt mixing process, the high temperature can easily lead to the degradation of biomass fibers, affecting the rutting resistance of the asphalt pavement; glass microbeads can effectively prevent the transfer of heat to the asphalt pavement, improve the thermal resistance of the asphalt pavement material, and avoid rutting caused by excessively high internal temperature of the asphalt pavement, but the glass microbeads have poor bonding with the asphalt matrix, and the glass microbeads are easily broken when subjected to external forces.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A biomass fiber reinforced rutting resistance asphalt pavement material comprises the following components: 60-80 parts of coarse aggregate, 20-40 parts of fine aggregate, 10-20 parts of 70# matrix asphalt, 6-8 parts of modified biomass fiber, 3-5 parts of limestone crushed stone and 2-3 parts of composite filler.

[0008] A method for preparing a biomass fiber reinforced asphalt pavement material with rutting resistance specifically comprises the following steps:

[0009] The coarse aggregate, fine aggregate and limestone crushed stone are mixed and preheated to obtain a preheated mixture; 70# base asphalt is placed in a mixing pot, heated to the mixing temperature, added into the preheated mixture, stirred for 1-3 minutes, and modified biomass fiber and composite filler are added, stirred and mixed for 3-5 minutes to obtain the asphalt pavement material.

[0010] Furthermore, the coarse aggregate is selected from basalt, and the apparent density is 2.7-3.1 g / cm 3 The water absorption rate is 1.5-1.6%, the crushing value is 15.2-17.3%, and the particle size is 9.5-13.2mm.

[0011] Furthermore, the fine aggregate is selected from mineral powder, which is S95 grade mineral powder with an apparent density of 2.6-2.7g / cm 3 , with a specific surface area of ​​450-500m 2 / kg, water content is 0.2-1%, and particle size is 3.2-4.3mm.

[0012] Furthermore, the crushing value index of limestone gravel is level two, 20%, and the compressive strength is 80-100MPa.

[0013] Furthermore, the preheating temperature is 160-180°C.

[0014] Furthermore, the mixing temperature is 160-190°C.

[0015] Furthermore, the modified biomass fiber is prepared by depositing the composite gel on the surface of the biomass fiber.

[0016] Furthermore, the biomass fiber is selected from any one of lignin fiber, straw fiber, bamboo fiber and bagasse fiber.

[0017] Furthermore, the biomass fiber has a diameter of 1-1.5 μm and a length of 2-10 μm.

[0018] More preferably, the biomass fiber has a diameter of 1.3 μm and a length of 8 μm.

[0019] Furthermore, the modified biomass fiber is specifically prepared by the following steps:

[0020] Anhydrous ethanol and deionized water were mixed and stirred evenly, KH550 was added, and the mixture was stirred for 30 minutes to completely hydrolyze KH550 to obtain a mixed solution, biomass fiber was added to the mixed solution, and the mixture was soaked for 90 minutes, and composite gel and 36% hydrochloric acid by mass fraction were added, and the mixture was stirred and reacted at 60°C for 10 minutes, filtered, and dried in an oven at 85°C for 30 minutes to obtain modified biomass fiber.

[0021] Among them, the hydroxyl groups produced by the hydrolysis of KH550 can be combined with the oxygen-containing functional groups on the surface of the biomass fiber through chemical bonds, and the amino groups of KH550 can be combined with the oxygen-containing functional groups on the surface of the composite gel under the catalysis of hydrochloric acid, so that the composite gel is deposited on the surface of the biomass fiber to form a gel layer with good high temperature resistance, avoiding the high temperature during the asphalt mixing process that can easily lead to the degradation of biomass fibers.

[0022] Furthermore, the mass ratio of anhydrous ethanol, deionized water, KH550, biomass fiber, and composite gel is (2-4):(6-8):(0.1-0.3):(0.1-0.2):(0.2-0.3).

[0023] Furthermore, the composite gel is prepared by mixing porous eggshell powder loaded with waste engine oil with thiol-modified silk fibroin and double-bonded hyaluronic acid and curing with ultraviolet light.

[0024] Furthermore, the UV curing wavelength is 360-380 nm and the curing time is 10-20 min.

[0025] Furthermore, the composite gel is specifically prepared by the following steps:

[0026] A1. The eggshells were washed, dried, and crushed in a grinder. The eggshell powder was placed in a blender, and agate balls and waste oil were added. After grinding at a speed of 300-400rpm for 25-35min, the agate balls were filtered and separated to obtain a porous eggshell powder loaded with waste oil;

[0027] Among them, after the eggshell powder is mechanically activated, the crushed eggshell powder collides with each other in the agate ball mixer to produce porous eggshell powder with a larger pore structure, which can adsorb the waste engine oil into the pores of the porous eggshell powder. Under the action of the high-energy ball milling mechanical force, a part of the waste engine oil is adsorbed onto the surface of the porous eggshell powder to form a waste engine oil layer with a positive charge.

[0028] Furthermore, the usage ratio of eggshell powder, agate balls and waste engine oil is (8-9) g:(2-4) g:(8-12) mL.

[0029] Furthermore, the particle size of the porous eggshell powder loaded with waste oil is 0.5-1 μm.

[0030] A2. Add double-bonded hyaluronic acid, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, tri(2-carbonylethyl)phosphine hydrochloride and thiolated silk fibroin into deionized water, stir evenly, add porous eggshell powder loaded with waste oil, stir evenly, place under ultraviolet lamp with a wavelength of 365nm, and cure for 15 minutes to obtain a composite gel.

[0031] Among them, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone is used as an initiator, which causes the thiol-olefin click reaction between the thiol-silk fibroin and the double-bonded hyaluronic acid under ultraviolet light to form a porous gel. The waste oil layer on the surface of the eggshell powder loaded with waste oil carries a positive charge and can combine with the hydroxyl and carboxyl groups in the thiol-silk fibroin and the double-bonded hyaluronic acid through hydrogen bonds, so that the eggshell powder loaded with waste oil is embedded in the porous gel.

[0032] Furthermore, the dosage ratio of double-bonded hyaluronic acid, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, tri(2-carbonylethyl)phosphine hydrochloride, thiolated silk fibroin, deionized water, and porous eggshell powder loaded with waste oil is (3-7) g:(0.3-0.5) g:(0.1-0.2) g:(5-5.4) g:(80-120) mL:(1-1.4) g.

[0033] Furthermore, the thiolated silk fibroin is prepared by the following steps:

[0034] 5.2 g of silk fibroin was added to 15 mL of ethanol and 60 mL of deionized water, stirred evenly to obtain a silk fibroin solution, placed in a dialysis bag with a molecular weight cutoff of 3500, dialyzed in deionized water at 4°C for 3 days, 1-ethyl-(3-dimethylaminopropyl)carbodiimide with a concentration of 0.3 mol / L and N-hydroxysuccinimide with a concentration of 0.5 mol / L were added, stirred for reaction for 30 minutes, 0.18 mol / L glutathione was added, stirred for reaction for 18 hours, dialyzed for 2 days according to the above dialysis process, and freeze-dried at -12°C for 10 minutes to obtain thiolated silk fibroin.

[0035] Among them, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide are used as catalysts to enable the hydroxyl groups in silk fibroin to react with the amine groups of reduced glutathione, thereby grafting reduced glutathione onto the silk fibroin molecular chain and giving it a reactive group thiol.

[0036] Furthermore, the amount ratio of silk fibroin, ethanol and deionized water is (5-5.4) g: (10-20) mL: (50-70) mL.

[0037] Further, the double-bonded hyaluronic acid is prepared by the following steps:

[0038] Add hyaluronic acid to deionized water, stir evenly, add N,N-dimethylformamide and methacrylic anhydride, stir and react at 4°C for 30 minutes, adjust the pH to 8.5 with 1 mol / L sodium hydroxide solution, continue stirring and reacting for 24 hours, add sodium chloride to break the emulsion for 1 hour, add anhydrous ethanol to form a white flocculent precipitate, take out the white precipitate by centrifugation, add to deionized water, dialyze in deionized water for 3 days at room temperature using a dialysis bag with a molecular weight cutoff of 7000, and freeze-dry to obtain double-bonded hyaluronic acid.

[0039] Among them, in the organic solvent N,N-dimethylformamide, the hydroxyl group in the hyaluronic acid can react with the anhydride group of methacrylic anhydride to achieve the grafting of methacrylic anhydride on the hyaluronic acid and impart reactive double bonds.

[0040] Furthermore, the dosage ratio of hyaluronic acid, deionized water, N,N-dimethylformamide and methacrylic anhydride is (1.6-2) g: (80-100) mL: (50-60) mL: (2-4) mL.

[0041] Furthermore, the composite filler is prepared by spraying a nano-carbon powder dispersion on the surface of modified glass microspheres.

[0042] Furthermore, the nano-carbon powder dispersion is prepared by mixing the nano-carbon powder and ethanol in a dosage ratio of (0.2-0.4) g:(30-40) mL.

[0043] Furthermore, the particle size of the nano carbon powder is 15-25nm and the specific surface area is 310.2-320.5m 2 / g, bulk density 0.8-0.9g / cm 3 .

[0044] Furthermore, the composite filler is specifically prepared by the following steps:

[0045] The nano-carbon powder dispersion was ultrasonically dispersed for 30 minutes, and the ultrasonically dispersed nano-carbon powder dispersion was sprayed onto the surface of the modified glass microbeads with a spray pen at a spraying distance of 10 cm. After the spraying was completed, it was placed in an oven at 85° C. and dried for 30 minutes to obtain a composite filler.

[0046] The nano-carbon powder dispersion is sprayed on the surface of the modified glass microspheres, so that the nano-carbon powder is embedded in the prepolymer on the surface of the modified glass microspheres, and the polar groups contained in the prepolymer can be combined with the nano-carbon powder, so that the nano-carbon powder can form a concave-convex rough surface on the surface of the modified glass microspheres.

[0047] Furthermore, the dosage ratio of the nano-carbon powder dispersion and the modified glass microbeads is (8-12) mL: (1-3) g.

[0048] Furthermore, the modified glass microbeads are prepared by modifying the surface of the bioadhesive glass microbeads and then reacting with the prepolymer.

[0049] Furthermore, the prepolymer is specifically prepared by the following steps: mixing terminal hydroxyl polybutadiene and 2,4-toluene diisocyanate, stirring and reacting at 50-70° C. for 10-20 minutes to obtain a prepolymer.

[0050] Furthermore, the usage ratio of terminal hydroxyl polybutadiene and 2,4-toluene diisocyanate is (8-12) mL:(2-3) g.

[0051] Furthermore, the modified glass microspheres are prepared by the following steps:

[0052] B1. Add the bioadhesive to ethanol, ultrasonically treat for 3 minutes at 500 W, centrifuge, and stir at 85°C until the ethanol evaporates to obtain purified bioadhesive. Add glass microbeads to 95% by mass ethanol aqueous solution, ultrasonically treat for 10 minutes, add purified bioadhesive, ultrasonically treat for 5 minutes, stir at 70°C for 2 hours, cool to room temperature, collect solids by centrifugation, wash the solids twice with acetone, wash three times with deionized water, and freeze-dry at -20°C for 10 minutes to obtain pretreated glass microbeads.

[0053] The multifunctional hydroxyl and amino groups contained in the bioadhesive can be combined with the hydroxyl groups on the surface of the glass microbeads through chemical bonds, so that the bioadhesive is coated on the surface of the glass microbeads, thereby improving the surface polarity of the glass microbeads.

[0054] Furthermore, the usage ratio of glass microbeads, ethanol aqueous solution, and purified bioadhesive is (0.3-0.7) g: (30-40) mL: (0.6-1) g.

[0055] B2. Add the pretreated glass microspheres to the prepolymer, stir and react for 2 h, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 30 min to obtain modified glass microspheres.

[0056] Among them, the hydroxyl groups contained in the glass microbeads coated with bioadhesive can react with the isocyanate groups of the prepolymer, so that the prepolymer containing carbamate and alkane groups is grafted on the surface of the glass microbeads. The carbamate and alkane groups contained can combine with the polar and non-polar components in the asphalt, so that the glass microbeads are evenly dispersed in the asphalt, enhancing the interaction between the glass microbeads and the asphalt.

[0057] Furthermore, the dosage ratio of the pretreated glass microbeads to the prepolymer is (0.3-0.7) g: (8-12) mL.

[0058] Furthermore, the bioadhesive is prepared by the following steps:

[0059] Put pig manure and deionized water in a reactor, stir evenly, heat to 340°C and pressure to 10.3MP, stir for 80 minutes, cool to room temperature, release the gas in the autoclave, reduce the pressure in the autoclave to 0.1MPa, take it out, filter to remove impurities, and obtain a bioadhesive.

[0060] Furthermore, the dosage ratio of pig manure and deionized water is (8-12) g:(13-17) mL.

[0061] Furthermore, compared with the prior art, the present invention has the following beneficial effects:

[0062] (1) In the technical scheme of the present invention, biological waste eggshell materials can improve the hardness and high temperature resistance of asphalt, reduce the plastic deformation and low temperature cracking performance of asphalt, and add eggshell powder to hot mix asphalt pavement materials to improve the resistance of asphalt pavement materials to moisture damage; porous eggshell powder is used to load waste engine oil, and the asphalt components are easily volatile during the aging process, so that the waste engine oil in the eggshell powder loaded with waste engine oil is released into the asphalt, so that the content of saturated components and aromatic components in the asphalt is maintained at a stable content, thereby reducing the aging degree of asphalt, and the powdery material of the eggshell powder loaded with waste engine oil added to the asphalt pavement material can be filled into the pores of the asphalt pavement material, thereby improving the density of the asphalt pavement material and improving the anti-rutting performance.

[0063] (2) In the technical scheme of the present invention, thiolated silk fibroin and double-bonded hyaluronic acid undergo thiol-olefin click reaction to form a porous gel, and the waste oil layer on the surface of the eggshell powder carrying waste oil carries a positive charge and can combine with the thiolated silk fibroin and double-bonded hyaluronic acid through hydrogen bonds, so that the eggshell powder carrying waste oil is embedded in the porous gel. The formed porous gel has a pore structure inside, has high compressive strength, and does not break after ten cycles. The compressive strength of the eggshell powder carrying waste oil is improved, and the eggshell powder in the asphalt pavement material is avoided from being broken due to external stress, which affects the anti-aging performance of the asphalt pavement. The cross-linking density of the gel is increased, and the pores of the porous gel are reduced, so as to avoid the formation of a porous gel with large pores, which causes the embedded eggshell powder carrying waste oil to fall off. In addition, the eggshell powder is filled into the gel to improve the high temperature resistance of the gel.

[0064] (3) In the technical solution of the present invention, the biomass fiber can pass through the micro-cracks in the asphalt pavement material, and can bear and transfer the load when the asphalt pavement material is subjected to stress, thereby effectively controlling the cracks and shrinkage of the asphalt pavement material and improving the crack resistance and rutting resistance of the asphalt pavement material. The composite gel is deposited on the surface of the biomass fiber to form a gel layer. On the one hand, the gel layer formed on the surface of the biomass fiber has good high temperature resistance, which can avoid the high temperature during the asphalt mixing process that may easily lead to the degradation of the biomass fiber. On the other hand, the composite gel is filled into the gaps in the asphalt along with the biomass fiber, and the composite gel can combine with the polar components in the asphalt to form a network mixed structure in the asphalt matrix, thereby improving the resilience of the asphalt pavement material, increasing its rutting resistance, and increasing the interaction and integrity of the asphalt system.

[0065] (4) In the technical solution of the present invention, the glass microspheres are a closed hollow structure, containing a large amount of inert gases such as N2 and CO2, and have excellent thermal insulation properties. They effectively prevent heat from being transferred to the asphalt pavement, improve the thermal resistance of the asphalt pavement material, thereby reducing the temperature of the middle and bottom layers, and avoiding the disadvantage of rutting caused by excessively high internal temperatures of the asphalt pavement; the bioadhesive is coated on the surface of the glass microspheres to increase the surface polarity of the glass microspheres. The hydroxyl groups contained in the bioadhesive can react with the isocyanate groups of the prepolymer, so that the prepolymer containing carbamate and alkane groups is grafted on the surface of the glass microspheres. The carbamate and alkane groups contained in the bioadhesive can combine with the polar and non-polar components in the asphalt, so that the glass microspheres are evenly dispersed in the asphalt, the interaction between the glass microspheres and the asphalt is enhanced, the thermal aging performance is improved, and the rutting resistance is improved. In addition, the bioadhesive reduces the mixing and compaction temperature of the asphalt matrix, thereby improving the processability of the asphalt and reducing the initial aging of the asphalt.

[0066] (5) In the technical solution of the present invention, a nano-carbon powder dispersion is sprayed on the surface of the modified glass microspheres, so that the nano-carbon powder is embedded in the prepolymer on the surface of the modified glass microspheres. The polar groups contained in the prepolymer can combine with the nano-carbon powder, thereby forming a concave-convex rough surface on the surface of the modified glass microspheres. The concave-convex structure increases the contact area with asphalt and improves the bonding ability of asphalt. When subjected to external force, the concave-convex structure formed by the nano-carbon powder can absorb stress and prevent the expansion of asphalt cracks. It can also avoid the breakage of the glass microspheres and improve the compressive strength. DETAILED DESCRIPTION

[0067] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0068] The raw materials used in the examples of the present invention are as follows: KH550 (AR, Macklin reagent); lignin fiber, straw fiber, bamboo fiber, bagasse fiber (Langfang Weichao New Materials Technology Co., Ltd.); glass microspheres (industrial grade, HL25, Zhengzhou Shenglait Hollow Microsphere New Materials Co., Ltd.); hydroxyl-terminated polybutadiene (molecular weight 3.8×10 3, hydroxyl value 0.47mmol / g, Tianyuan Aerospace Materials); 2,4-toluene diisocyanate (analytical grade, Tianjin Fuchen Chemical Reagent Factory); nanocarbon powder (Shanghai Xiaohuang Nanotechnology Co., Ltd.); hyaluronic acid (number average molecular weight of 100,000, Shandong Liyang Biotechnology Co., Ltd.); silk fibroin (Hubei Xinyuhong Biomedicine Technology Co., Ltd., purity 98%); glutathione (Hubei Shiteng Chemical Technology Co., Ltd.); methacrylic anhydride (product of Shanghai Aladdin Reagent Company).

[0069] The thiolated silk fibroin is prepared by the following steps:

[0070] 5.2 g of silk fibroin was added to 15 mL of ethanol and 60 mL of deionized water, stirred evenly to obtain a silk fibroin solution, placed in a dialysis bag with a molecular weight cutoff of 3500, dialyzed in deionized water at 4°C for 3 days, 1-ethyl-(3-dimethylaminopropyl)carbodiimide with a concentration of 0.3 mol / L and N-hydroxysuccinimide with a concentration of 0.5 mol / L were added, stirred for reaction for 30 minutes, 0.18 mol / L glutathione was added, stirred for reaction for 18 hours, dialyzed for 2 days according to the above dialysis process, and freeze-dried at -12°C for 10 minutes to obtain thiolated silk fibroin.

[0071] The double-bonded hyaluronic acid is specifically prepared by the following steps:

[0072] 1.8 g of hyaluronic acid was added to 90 mL of deionized water, and the mixture was stirred evenly. 55 mL of N,N-dimethylformamide and 3 mL of methacrylic anhydride were added, and the mixture was stirred and reacted at 4 °C for 30 min. The pH value was adjusted to 8.5 with 1 mol / L sodium hydroxide solution, and the mixture was stirred and reacted for 24 h. Then, 0.9 g of sodium chloride was added to break the emulsion for 1 h, and 400 mL of anhydrous ethanol was added to form a white flocculent precipitate. The white precipitate was taken out by centrifugation, and added to 100 mL of deionized water. The mixture was dialyzed in deionized water at room temperature for 3 d using a dialysis bag with a molecular weight cutoff of 7000, and the mixture was freeze-dried to obtain double-bonded hyaluronic acid.

[0073] The bioadhesive is specifically prepared by the following steps:

[0074] 10 g of pig manure and 15 mL of deionized water were placed in a reactor, stirred evenly, heated to 340°C and pressured to 10.3 MPa, stirred for 80 min, cooled to room temperature, released the gas in the autoclave, reduced the pressure in the autoclave to 0.1 MPa, took it out, filtered to remove impurities, and obtained a bioadhesive.

[0075] Example 1 The modified biomass fiber is prepared by the following steps:

[0076] A1. After washing and drying the eggshell, crush it in a grinder. Take 8.5g of eggshell powder and put it in a blender. Add agate balls and 10mL of waste oil. Grind at 300-400rpm for 25-35min, filter and separate the agate balls to obtain porous eggshell powder loaded with waste oil.

[0077] A2. Add 5 g of double-bonded hyaluronic acid, 0.4 g of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 0.15 g of tri(2-carbonylethyl)phosphine hydrochloride and 5.2 g of thiolated silk fibroin to 100 mL of deionized water, stir evenly, add 1.2 g of porous eggshell powder loaded with waste oil, stir evenly, place under an ultraviolet lamp with a wavelength of 365 nm, and cure for 15 minutes to obtain a composite gel.

[0078] A3. Mix 3g of anhydrous ethanol and 7g of deionized water, stir evenly, add 0.2g of KH550, stir for 30min to completely hydrolyze KH550 to obtain a mixed solution, add 0.15g of lignin fiber to the mixed solution, soak for 90min, add 0.3g of composite gel and 0.2mL of 36% hydrochloric acid, stir and react at 60°C for 10min, filter, and dry in an oven at 85°C for 30min to obtain modified biomass fiber.

[0079] Comparative Example 1 The difference between this comparative example and Example 1 is that the composite gel is replaced by porous eggshell powder loaded with waste engine oil, and the remaining steps and raw materials are the same as Example 1.

[0080] A1. After washing and drying the eggshell, crush it in a grinder. Take 8.5g of eggshell powder and put it in a blender. Add agate balls and 10mL of waste oil. Grind at 300-400rpm for 25-35min, filter and separate the agate balls to obtain porous eggshell powder loaded with waste oil.

[0081] A2. Mix 3g of anhydrous ethanol and 7g of deionized water, stir evenly, add 0.2g of KH550, stir for 30min to completely hydrolyze KH550 to obtain a mixed solution, add 0.15g of lignin fiber to the mixed solution, soak for 90min, add 0.3g of porous eggshell powder loaded with waste oil and 0.2mL of 36% hydrochloric acid, stir and react at 60°C for 10min, filter, and dry in an oven at 85°C for 30min to obtain modified biomass fiber.

[0082] Comparative Example 2 The difference between this comparative example and Example 1 is that the composite gel is not deposited on the surface of the biomass fiber, and the remaining steps and raw materials are the same as those in Example 1.

[0083] A1. After washing and drying the eggshell, crush it in a grinder. Take 8.5g of eggshell powder and put it in a blender. Add agate balls and 10mL of waste oil. Grind at 300-400rpm for 25-35min, filter and separate the agate balls to obtain porous eggshell powder loaded with waste oil.

[0084] A2. Add 5 g of double-bonded hyaluronic acid, 0.4 g of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 0.15 g of tri(2-carbonylethyl)phosphine hydrochloride and 5.2 g of thiolated silk fibroin to 100 mL of deionized water, stir evenly, add 1.2 g of porous eggshell powder loaded with waste oil, stir evenly, place under an ultraviolet lamp with a wavelength of 365 nm, and cure for 15 minutes to obtain a composite gel.

[0085] A3. 0.15 g of lignin fiber and 0.3 g of composite gel were mixed to obtain modified biomass fiber.

[0086] Example 2 The composite filler is prepared by the following steps:

[0087] B1. Add 10 g of bioadhesive to 16 mL of ethanol, ultrasonically treat at 500 W for 3 min, centrifuge, and stir at 85°C until the ethanol evaporates to obtain purified bioadhesive; add 0.5 g of glass microbeads to 35 mL of 95% by mass ethanol aqueous solution, ultrasonically treat for 10 min, add 0.8 g of purified bioadhesive, ultrasonically treat for 5 min, stir at 70°C for 2 h, cool to room temperature, collect solids by centrifugation, wash the solids twice with acetone, wash three times with deionized water, and freeze-dry at -20°C for 10 min to obtain pretreated glass microbeads.

[0088] B2. Mix 10 mL of terminal hydroxyl polybutadiene and 2.5 g of 2,4-toluene diisocyanate, stir and react at 60°C for 15 min to obtain a prepolymer, add 0.5 g of pretreated glass beads to 10 mL of the prepolymer, stir and react for 2 h, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 30 min to obtain modified glass beads.

[0089] B3. Ultrasonic disperse 10 mL of nano-carbon powder dispersion for 30 minutes, spray the ultrasonically dispersed nano-carbon powder dispersion onto the surface of 2 g of modified glass microbeads with a spray pen at a spraying distance of 10 cm. After spraying, place it in an oven at 85°C and dry it for 30 minutes to obtain a composite filler, wherein the nano-carbon powder dispersion is a mixture of nano-carbon powder and ethanol in a dosage ratio of (0.2-0.4) g:(30-40) mL.

[0090] Comparative Example 3 The difference between this comparative example and Example 2 is that the pre-treated glass microspheres are replaced with glass microspheres, and the remaining steps and raw materials are the same as Example 2.

[0091] B1. 10 mL of hydroxy-terminated polybutadiene and 2.5 g of 2,4-toluene diisocyanate were mixed, and the mixture was stirred and reacted at 60°C for 15 min to obtain a prepolymer. 0.5 g of glass microspheres were added to 10 mL of the prepolymer, and the mixture was stirred and reacted for 2 h. The mixture was filtered, washed with deionized water for 3 times, and dried in an oven at 70°C for 30 min to obtain modified glass microspheres.

[0092] B2. Ultrasonic disperse 10 mL of nano-carbon powder dispersion for 30 minutes, spray the ultrasonically dispersed nano-carbon powder dispersion onto the surface of 2 g of modified glass microbeads with a spray pen at a spraying distance of 10 cm. After spraying, place it in an oven at 85°C and dry it for 30 minutes to obtain a composite filler, wherein the nano-carbon powder dispersion is a mixture of nano-carbon powder and ethanol in a dosage ratio of (0.2-0.4) g:(30-40) mL.

[0093] Comparative Example 4 The difference between this comparative example and Example 2 is that the nano-carbon powder dispersion is not sprayed on the surface of the modified glass microspheres, and the remaining steps and raw materials are the same as those in Example 2.

[0094] B1. Add 10 g of bioadhesive to 16 mL of ethanol, ultrasonically treat at 500 W for 3 min, centrifuge, and stir at 85°C until the ethanol evaporates to obtain purified bioadhesive; add 0.5 g of glass microbeads to 35 mL of 95% by mass ethanol aqueous solution, ultrasonically treat for 10 min, add 0.8 g of purified bioadhesive, ultrasonically treat for 5 min, stir at 70°C for 2 h, cool to room temperature, collect solids by centrifugation, wash the solids twice with acetone, wash three times with deionized water, and freeze-dry at -20°C for 10 min to obtain pretreated glass microbeads.

[0095] B2. Mix 10 mL of terminal hydroxyl polybutadiene and 2.5 g of 2,4-toluene diisocyanate, stir and react at 60°C for 15 minutes to obtain a prepolymer, add 0.5 g of pretreated glass beads to 10 mL of the prepolymer, stir and react for 2 hours, filter, wash with deionized water three times, and dry in an oven at 70°C for 30 minutes to obtain a composite filler.

[0096] Example 3 A biomass fiber reinforced rutting resistance asphalt pavement material includes the following components: 60 parts of coarse aggregate, 20 parts of fine aggregate, 10 parts of 70# matrix asphalt, 6 parts of modified biomass fiber, 3 parts of limestone gravel, and 2 parts of composite filler.

[0097] A method for preparing a biomass fiber reinforced asphalt pavement material with rutting resistance specifically comprises the following steps:

[0098] Coarse aggregate, fine aggregate and limestone gravel are mixed, and preheated at 170°C for 1 minute to obtain a preheated mixture; 70# base asphalt is placed in a mixing pot, heated to 175°C, mixed, added to the preheated mixture, stirred for 2 minutes, and modified biomass fiber and composite filler are added, stirred and mixed for 4 minutes to obtain asphalt pavement material.

[0099] Example 4 A biomass fiber reinforced rutting resistance asphalt pavement material includes the following components: 70 parts of coarse aggregate, 30 parts of fine aggregate, 15 parts of 70# matrix asphalt, 7 parts of modified biomass fiber, 4 parts of limestone gravel, and 2.5 parts of composite filler.

[0100] A method for preparing a biomass fiber reinforced asphalt pavement material with rutting resistance specifically comprises the following steps:

[0101] Coarse aggregate, fine aggregate and limestone gravel are mixed, and preheated at 170°C for 1 minute to obtain a preheated mixture; 70# base asphalt is placed in a mixing pot, heated to 175°C, mixed, added to the preheated mixture, stirred for 2 minutes, and modified biomass fiber and composite filler are added, stirred and mixed for 4 minutes to obtain asphalt pavement material.

[0102] Example 5 A biomass fiber reinforced rutting resistance asphalt pavement material includes the following components: 80 parts of coarse aggregate, 40 parts of fine aggregate, 20 parts of 70# matrix asphalt, 8 parts of modified biomass fiber, 5 parts of limestone gravel, and 3 parts of composite filler.

[0103] A method for preparing a biomass fiber reinforced asphalt pavement material with rutting resistance specifically comprises the following steps:

[0104] Coarse aggregate, fine aggregate and limestone gravel are mixed, and preheated at 170°C for 1 minute to obtain a preheated mixture; 70# base asphalt is placed in a mixing pot, heated to 175°C, mixed, added to the preheated mixture, stirred for 2 minutes, and modified biomass fiber and composite filler are added, stirred and mixed for 4 minutes to obtain asphalt pavement material.

[0105] Comparative Example 5 The difference between this comparative example and Example 4 is that the modified biomass fiber is replaced by the material prepared in Comparative Example 1, and the remaining steps and raw materials are the same as Example 4.

[0106] Comparative Example 6 The difference between this comparative example and Example 4 is that the modified biomass fiber is replaced by the material prepared in Comparative Example 2, and the remaining steps and raw materials are the same as those in Example 4.

[0107] Comparative Example 7 The difference between this comparative example and Example 4 is that the composite filler is replaced by the material prepared in Comparative Example 3, and the remaining steps and raw materials are the same as those in Example 4.

[0108] Comparative Example 8 The difference between this comparative example and Example 4 is that the composite filler is replaced by the material prepared in Comparative Example 4, and the remaining steps and raw materials are the same as those in Example 4.

[0109] The performance of the asphalt pavement materials prepared in Examples 3-5 and Comparative Examples 5-8 was tested;

[0110] The high temperature rutting test, low temperature beam bending test and immersion Marshall test were carried out according to the T0719-2011, T0715-2011 and T0709-2011 methods in JTGE20-2011 "Testing Procedures for Asphalt and Asphalt Mixtures in Highway Engineering"

[16] respectively, to measure the rutting resistance, compressive strength and stability of the asphalt pavement material prepared above. The asphalt pavement material was placed in an aging test box, and the aging lamp used a 420W high-pressure mercury lamp with an aluminum reflector lampshade. The irradiation time of the high-pressure mercury lamp was 72 hours, and the softening point (℃) and ductility (mm) of the asphalt pavement material were recorded; the results are shown in Table 1 below:

[0111]

[0112] It can be seen from the data in Table 1 that in Comparative Example 5, the composite gel is replaced with a modified biomass fiber prepared by porous eggshell powder loaded with waste engine oil and added to the asphalt pavement material, and its thermal aging performance and anti-rutting performance are reduced. This may be because the eggshell powder loaded with waste engine oil is embedded in the porous gel and has a high compressive strength, thereby improving the compressive strength of the eggshell powder loaded with waste engine oil, thereby avoiding the eggshell powder from breaking due to external stress in the asphalt pavement material, thereby affecting the anti-aging performance and anti-rutting performance of the asphalt pavement; in Comparative Example 6, the modified biomass fiber prepared by not depositing the composite gel on the surface of the biomass fiber is added to the asphalt pavement material, and its anti-rutting performance is reduced. This may be because a gel layer is formed on the surface of the biomass fiber, which has good high temperature resistance, thereby avoiding the high temperature during the asphalt mixing process, which easily leads to the degradation of the biomass fiber and affects the anti-rutting performance; in Comparative Example 7, the pretreated glass beads are replaced with glass When the composite filler prepared by microbeads is added to the asphalt pavement material, its anti-rutting performance and aging resistance are reduced. This may be because the bioadhesive is coated on the surface of the glass microbeads and can react with the isocyanate group of the prepolymer, so that the prepolymer containing carbamate and alkane groups is grafted on the surface of the glass microbeads, thereby enhancing the interaction between the glass microbeads and asphalt, and improving the thermal aging performance and anti-rutting performance; in Example 8, the composite filler prepared by not spraying the nano-carbon powder dispersion on the surface of the modified glass microbeads is added to the asphalt pavement material, and its anti-rutting performance and aging resistance are reduced. This may be because a concave-convex rough surface is formed on the surface of the modified glass microbeads, and its concave-convex structure increases the contact area with asphalt and improves the bonding ability of asphalt. When subjected to external force, the concave-convex structure formed by the nano-carbon powder can absorb stress, prevent the expansion of asphalt cracks, and avoid the breakage of the glass microbeads, thereby improving the compressive strength.

[0113] The data in Table 1 show that the asphalt pavement materials prepared in Examples 3-5 have good anti-rutting and aging resistance and meet the test performance requirements, while the asphalt pavement materials prepared in Comparative Examples 5-8 do not meet the performance requirements, indicating that the asphalt pavement materials prepared in the present invention have good anti-rutting and aging resistance.

[0114] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0115] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A biomass fiber reinforced rutting resistance asphalt pavement material, characterized in that: It includes the following components: 60-80 parts of coarse aggregate, 20-40 parts of fine aggregate, 10-20 parts of 70# matrix asphalt, 6-8 parts of modified biomass fiber, 3-5 parts of limestone crushed stone, and 2-3 parts of composite filler; The modified biomass fiber is prepared by depositing a composite gel on the surface of the biomass fiber; The modified biomass fiber is specifically prepared by the following steps: mixing anhydrous ethanol and deionized water, stirring evenly, adding KH550, stirring for 30 minutes to completely hydrolyze KH550 to obtain a mixed solution, adding biomass fiber to the mixed solution, soaking for 90 minutes, adding composite gel and hydrochloric acid with a mass fraction of 36%, stirring and reacting at 60° C. for 10 minutes, filtering, and drying in an oven at 85° C. for 30 minutes to obtain the modified biomass fiber; The composite gel is prepared by mixing porous eggshell powder loaded with waste engine oil, thiol-modified silk fibroin and double-bonded hyaluronic acid, and curing with ultraviolet light; The composite gel is specifically prepared by the following steps: A1. The eggshells were washed, dried, and crushed in a grinder. The eggshell powder was placed in a blender, and agate balls and waste oil were added. After grinding at a speed of 300-400rpm for 25-35min, the agate balls were filtered and separated to obtain a porous eggshell powder loaded with waste oil; A2. Add double-bonded hyaluronic acid, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, tri(2-carbonylethyl)phosphine hydrochloride and thiolated silk fibroin to deionized water, stir evenly, add porous eggshell powder loaded with waste oil, stir evenly, place under ultraviolet light with a wavelength of 365nm, and cure for 15min to obtain a composite gel; The composite filler is prepared by spraying a nano-carbon powder dispersion on the surface of modified glass microspheres; The composite filler is specifically prepared by the following steps: The nano-carbon powder dispersion was ultrasonically dispersed for 30 minutes, and the nano-carbon powder dispersion was sprayed onto the surface of the modified glass microspheres with a spray pen at a spraying distance of 10 cm. After the spraying was completed, the nano-carbon powder dispersion was placed in an oven at 85° C. and dried for 30 minutes to obtain a composite filler; The modified glass microbeads are prepared by reacting bioadhesive surface-modified glass microbeads with prepolymers; The modified glass microspheres are specifically prepared by the following steps: B1. Add the bioadhesive to ethanol, ultrasonically treat for 3 minutes at 500W, centrifuge, stir at 85°C until the ethanol evaporates to obtain purified bioadhesive, add glass microbeads to 95% ethanol aqueous solution by mass, ultrasonically treat for 10 minutes, add purified bioadhesive, ultrasonically treat for 5 minutes, stir at 70°C for 2 hours, cool to room temperature, collect solids by centrifugation, wash the solids twice with acetone, wash three times with deionized water, and freeze-dry at -20°C for 10 minutes to obtain pretreated glass microbeads; B2. The pretreated glass beads were added to the prepolymer, stirred for 2 h, filtered, washed with deionized water 3 times, and dried in an oven at 70 ° C for 30 min to obtain modified glass beads; The prepolymer is specifically prepared by the following steps: mixing terminal hydroxyl polybutadiene and 2,4-toluene diisocyanate, stirring and reacting at 50-70° C. for 10-20 minutes to obtain the prepolymer.

2. The biomass fiber reinforced rutting resistance asphalt pavement material according to claim 1, characterized in that: The biomass fiber is selected from any one of lignin fiber, straw fiber, bamboo fiber and bagasse fiber; the biomass fiber has a diameter of 1-1.5 μm and a length of 2-10 μm.

3. The biomass fiber reinforced rutting resistance asphalt pavement material according to claim 1, characterized in that: The porous eggshell powder loaded with waste engine oil is specifically prepared by the following steps: The eggshells are washed and dried, and then crushed in a grinder. The eggshell powder is placed in a mixer, and agate balls and waste engine oil are added. After grinding at a speed of 300-400 rpm for 25-35 minutes, the agate balls are filtered and separated to obtain porous eggshell powder loaded with waste engine oil. The usage ratio of the eggshell powder, agate balls and waste engine oil is (8-9) g:(2-4) g:(8-12) mL.

4. The biomass fiber reinforced rutting resistance asphalt pavement material according to claim 1, characterized in that: The ultraviolet light curing wavelength is 360-380nm, and the time is 10-20min.

5. The biomass fiber reinforced rutting resistance asphalt pavement material according to claim 1, characterized in that: The nano-carbon powder dispersion is prepared by mixing nano-carbon powder and ethanol in a dosage ratio of (0.2-0.4) g:(30-40) mL.

6. The biomass fiber reinforced rutting resistance asphalt pavement material according to claim 5, characterized in that: The nano carbon powder has a particle size of 15-25 nm and a specific surface area of ​​310.2-320.5 m 2 / g, bulk density 0.8-0.9g / cm 3 .

7. The biomass fiber reinforced rutting resistance asphalt pavement material according to claim 1, characterized in that: The coarse aggregate is selected from basalt, and the apparent density is 2.7-3.1 g / cm 3 The water absorption rate is 1.5-1.6%, the crushing value is 15.2-17.3%, and the particle size is 9.5-13.2mm.

8. The biomass fiber reinforced rutting resistance asphalt pavement material according to claim 1, characterized in that: The fine aggregate is selected from mineral powder, which is S95 grade mineral powder with an apparent density of 2.6-2.7 g / cm 3 , with a specific surface area of ​​450-500m 2 / kg, water content is 0.2-1%.

9. The method for preparing a biomass fiber reinforced rutting resistance asphalt pavement material according to claim 1, characterized in that: The specific steps include: The coarse aggregate, fine aggregate and limestone crushed stone are mixed and preheated to obtain a preheated mixture; 70# base asphalt is placed in a mixing pot, heated to the mixing temperature, added into the preheated mixture, stirred for 1-3 minutes, and modified biomass fiber and composite filler are added, stirred and mixed for 3-5 minutes to obtain the asphalt pavement material.

Citation Information

Patent Citations

  • Rutting resistant bituminous mixture and preparation method thereof

    CN110550886A

  • Asphalt concrete suitable for low-heat valley area and preparation method thereof

    CN112250347A

  • Modified asphalt mortar based on green composite filler and preparation method thereof

    CN113801487A

  • Silk fibroin-based hydrogel double-layer composite membrane and preparation method thereof

    CN117339022A